The Influence of Visual Effects on Viewer Behavior: AI Integration, Marketing Strategy, and HR Perspectives in Television Content Management - Khanna, Lakshey; Khandelwal, Vidhi (Journal of Neonatal Surgery, 2025)
Aim: In this case, Visual Effects (VE), AI Integration (AI), and Marketing Strategy (MS) are the independent variables, and Viewer Behavior (VB) in digital media platforms is the dependent variable to be studied. It aims at determining what factors have the strongest effect on audiences and content consumption behaviours. Methodology: Quantitative cross-sectional research design was applied. The study IE used primary data that was obtained through a structured questionnaire administered to 412 respondents who were asked to respond based on the four constructs. Multiple Likert items on the basis of validated scales in previous literature were used to measure each construct. Statistical Methods: Descriptive statistics, reliability analysis (Cronbach Alpha), normality test (Shapiro-Wilk), Pearson correlation, and multiple linear regression analysis were performed to analyze the data and test the hypotheses and the relationship between the variables. Results: The three independent variables, including visual effects, AI integration, and marketing strategy, showed significant and positive impacts on the viewer behavior (p < 0.001). The regression model demonstrated a high predictive performance (R 2 =0.555), and the AI integration became the most significant predictor. Originality/Value: This paper is relevant to the field of research based on providing the integrated model of visual, technological, and strategic factors influencing viewer behavior. It offers practical recommendations to content developers, marketers and platform designers interested in maximizing viewer participation in the digital era.